2007
DOI: 10.1021/jp068954k
|View full text |Cite
|
Sign up to set email alerts
|

Contrary Hydration Behavior of N-Isopropylacrylamide to its Polymer, P(NIPAm), with a Lower Critical Solution Temperature

Abstract: The number of hydrated water molecules per N-isopropylacrylamide in homogeneous aqueous solution was determined to be a constant with a value of 5-6 below and above the lower critical solution temperature, LCST (32 degrees C), of its polymer, poly(N-isopropylacrylamide), by high-frequency dielectric relaxation techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
173
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(193 citation statements)
references
References 10 publications
19
173
0
1
Order By: Relevance
“…29,30 They cannot be observed in the selected frequency range as in characteristic relaxation processes. However, conductivity related phenomena like the drift motion of charge carriers (DC-conductivity) and/or interfacial polarization effects such as Maxwell-Wagner-Sillars (MWS) polarization can be detected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 They cannot be observed in the selected frequency range as in characteristic relaxation processes. However, conductivity related phenomena like the drift motion of charge carriers (DC-conductivity) and/or interfacial polarization effects such as Maxwell-Wagner-Sillars (MWS) polarization can be detected.…”
Section: Resultsmentioning
confidence: 99%
“…It allows investigations of the molecular structure by taking the molecular mobility and/or the conductivity as a probe. 27 Ono and Shikata 28,29 applied dielectric spectroscopy at high frequencies (1.6 Â 10 6 Hz to 1.6 Â 10 11 Hz) in order to study the hydration and molecular dynamics of linear pNIPAM in aqueous solutions at temperatures between 6 C and 39 C. The temperature dependence of the (de)hydration behaviour of the monomer NIPAM and the polymer pNIPAM was investigated by analyzing the dynamics of water molecules hydrated to the solute. The relaxation processes of linear pNIPAM and solvent molecules as a function of polymer concentration and type of solvent have been studied by Nakano et al 30 Dielectric spectroscopy was applied in a frequency range from 4 Â 10 4 Hz to 2 Â 10 10 Hz at a temperature of 25 C. Two relaxation processes could be detected due to the fluctuations of the polymer segments (MHz range) and the solvent molecules (GHz range).…”
mentioning
confidence: 99%
“…The simulated network shown schematically in Figure 9a and atomistically in Figure 9b is similar to that identified in the experimental studies of Ono and Shikata. 25 Note that this network between two adjacent monomers comprises five water molecules. which is in good agreement with the experimentally reported value in ref 25. In addition to the conformation shown in Figure 9, we also observe another conformation of water-polymer network (shown in Figure 10).…”
Section: Resultsmentioning
confidence: 99%
“…6 for amide groups of low mass compounds. 13 The positive n H values for these compounds definitely reveal that these polar groups with DN values higher than 18 are hydrophilic because of the formation of hydrogen bonds between the polar groups and water molecules.…”
Section: ■ Introductionmentioning
confidence: 92%
“…6 for amide groups of low mass compounds. 13 The positive n H values for these compounds definitely reveal that these polar groups with DN values higher than 18 are hydrophilic because of the formation of hydrogen bonds between the polar groups and water molecules.There exist other types of water-soluble compounds possessing highly polar groups with dipole moments greater than 3.0 D. Although nitro compounds, such as nitro methane (MeNO 2 ) and nitro ethane (EtNO 2 ) bearing a nitro group (NO 2 ) with the large dipole moment of 3.4 D, but a low DN value of 3−4, are water-soluble, 1-nitropropane (PrNO 2 ) only slightly larger than EtNO 2 possesses a low water solubility of 0.17 M. 14 Very recently, dielectric spectroscopic measurements have revealed that the hydration number of the NO 2 group is n H = 0. 14 Then, the relatively high water solubility of MeNO 2 and EtNO 2 are not caused by the hydration effect of the NO 2 group.…”
mentioning
confidence: 92%